2021
DOI: 10.1111/cgf.14298
|View full text |Cite
|
Sign up to set email alerts
|

Accessible Visualization: Design Space, Opportunities, and Challenges

Abstract: Visualizations are now widely used across disciplines to understand and communicate data. The benefit of visualizations lies in leveraging our natural visual perception. However, the sole dependency on vision can produce unintended discrimination against people with visual impairments. While the visualization field has seen enormous growth in recent years, supporting people with disabilities is much less explored. In this work, we examine approaches to support this marginalized user group, focusing on visual d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 116 publications
0
35
0
Order By: Relevance
“…The lack of rationale for caption guidelines raises the need to analyze captions systematically. While the three-level model by Kim et al [8] guides people on how to scaffold visualization information in order, Lundgard et al [11] propose a concrete model that categorizes the content in a caption into four semantic levels: 1) elemental and encoded, 2) statistical and relational, 3) perceptual and cognitive, and 4) contextual and domain-specific (Table 1).…”
Section: Natural Language Models For Captionsmentioning
confidence: 99%
“…The lack of rationale for caption guidelines raises the need to analyze captions systematically. While the three-level model by Kim et al [8] guides people on how to scaffold visualization information in order, Lundgard et al [11] propose a concrete model that categorizes the content in a caption into four semantic levels: 1) elemental and encoded, 2) statistical and relational, 3) perceptual and cognitive, and 4) contextual and domain-specific (Table 1).…”
Section: Natural Language Models For Captionsmentioning
confidence: 99%
“…Largely, access issues other than vision that affect data visualization (such as cognitive/neurological, vestibular, and motor concerns) are almost entirely unserved in this research space. Kim et al found that 56 papers have been published between 1999 and 2020 that focus on vision‐related accessibility (not including color vision deficiency), with only 3 being published at a visualization venue (and only recently since 2018) [KJRK21]. Marriott et al found that there is no research at all that engages motor accessibility [MLB∗21].…”
Section: Existing Work In Data Visualization and Accessibilitymentioning
confidence: 99%
“…While not aiming at supporting people with impairment specifically, several techniques have been proposed to automatically generate captions for visualizations [31,21,54,44,45,18,59,86,16]. A more thorough survey on accessible visualizations can be found [47].…”
Section: Visualization Accessibility For Visually Impaired Peoplementioning
confidence: 99%